Information, overconﬁdence and trading : do the sources of information matter? - Abreu, Margarida (2015)
We investigate how the strength of the positive association between frequency of trading and information acquisition is dependent on the sources of information used by investors and on investors’ overconﬁdence. We add to the existing literature by investigating if the positive relationship between investment in information and intensity of trading in ﬁnancial assets is sensitive to the sources of information used by investors, and if this inﬂuence is different for overconﬁdent and non-overconﬁdent investors. Our results conﬁrm the classical statement that the more frequently individual investors invest in information, the more they trade in ﬁnancial products. They also conﬁrm behavioral ﬁnance ﬁndings that overconﬁdent investors, who show a better than average bias, trade more frequently. Our ﬁndings are novel showing that the more overconﬁdent and non-overconﬁdent investors invest in information the more they trade, but the trading behavior is sensitive to the sources of information used. Overconﬁdent investors trade less frequently when they collect information via friends and family, and non-overconﬁdent investors trade more frequently when they use specialized sources of information.